Wawasan Al-Qur’an dan Alkitab Tentang Term Kafir: Sebuah Studi Komparatif - Rahmatullah, (QOF, 2022)
The term of kafir is one of the most sensitive and controversial terms in religious texts. In religious texts such as the Qur'an and the Bible, the term kafir is discussed or mentioned. However, the discussion of the term kafir in the framework of a comparative study between the two holy books is still rare, especially those that relate it to the Indonesian context. This study aimed to fill that gap. By doing so, it gained a better understanding of the term kafir from the perspective of religious scriptures. This study was a literature study of the Qur'an and Bible, supplemented by various relevant secondary sources. As a result, this study found that the term kafir in the Qur'an is very diverse and dynamic. The term kafir in the Bible is quite a few and is not as dynamic as the Qur'an. Generally, the Qur'an explains the term kafir as a certain attitude or act of disbelief, while the Bible is more about the information on certain things that are not related to certain attitudes or actions. In general, the term kafir from the perspective of the two holy books is seen as a term that is negatively charged. That is why the term kafir is generally sensitive and controversial, especially in Indonesia, so using this term in the Indonesian context needs to be based on considerations that prioritize common interests. The humanitarian aspect is one of the common interests that need to be prioritized or prioritized to avoid various negative impacts that can be triggered by this term on the state of a country with rich diversity like Indonesia.